Entanglement and Bell inequality violation in vector diboson systems produced in decays of spin-0 particles - Alexander Bernal; Paweł Caban; Jakub Rembieliński (Scientific Reports)
Abstract We discuss entanglement and the violation of the Collins–Gisin–Linden–Massar–Popescu (CGLMP) inequality in a system of two vector bosons produced in the decay of a spin-0 particle. We assume the most general CPT conserving, Lorentz- invariant coupling of the spin-0 particle with the daughter bosons. We compute the most general two-boson density matrix obtained by averaging over kinematical configurations with an appropriate probability distribution (which can be obtained when both bosons subsequently decay into fermion–antifermion). We show that the two-boson state is entangled and violates the CGLMP inequality for all values of the (anomalous) coupling constants and that in this case the state is entangled iff it can violate the CGLMP inequality. As an exemplary process of this kind we use the decay $$H→ ZZ$$ with anomalous coupling.